Internet Regulation in Egypt: Outcomes and Policy Recommendations - ElDemerdash, Sara (AUC Knowledge Fountain, 2021)
With the rapid developments the Internet is witnessing, the topic of internet regulation sees itself taking center stage in a rising global debate among many stakeholders. This debate centers around hot topics and fundamentals such as the rights of free speech and access to information, intellectual property, as well as user and data privacy, and security issues. Egypt is no exception; especially after the uprising and mass demonstrations in 2011 and the growing concerns around internet regulation and freedom of expression. This thesis aims at examining the development process of the current Internet regulation policy in Egypt to study its outcomes on the freedom of the internet and online journalism. The thesis will start with a narrative discussion on the historical development of internet regulation, followed by a comparative study between the progression and current regulation efforts in some of the developed and developing countries around the world such as China, Singapore, The European Union, The United Kingdom, Germany, Tunisia and Egypt, to examine the progression of policies from mass media to the Internet. Data on Egypt will be collected through conducting a qualitative research with policy makers, the private sector and civil society journalism. The thesis will conclude with policy recommendations to the Egyptian Supreme Council for Media Regulation.